The digital frontier as a liminal space - Belk, Russell (Journal of Consumer Psychology, 2024)
AbstractHadi et al. (Journal of Consumer Psychology, 34, 2023) have created a masterful and wide‐sweeping review of the consumer behavior literature on the Metaverse. They envision our encounter with the Metaverse as a consumer journey. In this commentary, I highlight some of their unique contributions and suggest additional insights that emerge when we view the digital frontier as a liminal place betwixt and between now and then, here and there, and reality and virtuality. The Metaverse is also a metaphor and I entertain three metaphoric interpretations. First, the Metaverse is an experience machine of the sort that Robert Nozick imagined in his thought experiment involving real and artificial pleasures. Alternatively, consumers themselves can be seen as desiring machines as Gilles Deleuze and Féliz Guattari characterized them, and the Metaverse can be seen as an instantiation of our collective desires. Or thirdly, the Metaverse can be regarded as a shared hallucination. As these diverse metaphors suggest, imagining the metaverse is a projective exercise. But the consequences may involve up to a trillion dollars in revenues, so I hope these provocations prove useful whether they are ultimately borne out or not.